2005
DOI: 10.1103/physrevd.72.043527
|View full text |Cite
|
Sign up to set email alerts
|

Dark-energy evolution across the cosmological-constant boundary

Abstract: We explore the properties of dark energy models for which the equation-of-state, w, defined as the ratio of pressure to energy density, crosses the cosmological-constant boundary w = −1. We adopt an empirical approach, treating the dark energy as an uncoupled fluid or a generalized scalar field. We describe the requirements for a viable model, in terms of the equation-of-state and sound speed. A generalized scalar field cannot safely traverse w = −1, although a pair of scalars with w > −1 and w < −1 will work.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 40 publications
3
129
0
Order By: Relevance
“…This is in fact the kind of crossing discussed specifically in [41] and [42]. The question, motivated by persistent observational suggestions that w may indeed currently be less than −1 [and also by analyses showing that better fits to the data [47] are obtained by models which cross the phantom divide in recent times], is whether string gas cosmologies can sustain NEC violation not just briefly, in the extremely early Universe, but also over cosmologically significant periods.…”
Section: The Global Formulation Of String Gas Spacetimesmentioning
confidence: 99%
“…This is in fact the kind of crossing discussed specifically in [41] and [42]. The question, motivated by persistent observational suggestions that w may indeed currently be less than −1 [and also by analyses showing that better fits to the data [47] are obtained by models which cross the phantom divide in recent times], is whether string gas cosmologies can sustain NEC violation not just briefly, in the extremely early Universe, but also over cosmologically significant periods.…”
Section: The Global Formulation Of String Gas Spacetimesmentioning
confidence: 99%
“…If a DE evolves from one regime to another, this is called phantom crossing, but [27], e.g., showed that this is impossible for a purely kinetic k-essence. We refer to [28,29] for a discussion of phantom crossing in the context of other DE models.…”
Section: The Modelmentioning
confidence: 99%
“…Extended models where the scalar * Electronic address: n.tamanini.11@ucl.ac.uk field Lagrangian is a general function of both the scalar field φ and its kinetic term, are known as k-essence theories [11]. Within this framework it is possible to obtain not only the standard dark energy evolution but also the so called phantom regime and quintessence to phantom transition, though fatal problems always arise at the level of perturbations [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However in this model the scalar field EoS parameter is never greater than −1 creating problems at early times where dark matter with vanishing pressure must dominate. Scalar fields which can cross the phantom barrier at w φ = −1 are usually dubbed quintom models and imply either the use of extended Lagrangians, generally instable, or of two different scalar fields [14,18].…”
Section: Introductionmentioning
confidence: 99%